Corona Virus Disease 19 (COVID-19) Patient Profile in Klungkung - Sepriyanti, Ni Komang Ari; Winaya, Erwin; Putra, I Wayan Ardyan Sudharta (Jurnal Respirasi, 2024)
Introduction: Despite the effective global mass vaccination programs, which included booster shots, the emergence of new SARS-CoV-2 strains threatens to undo the enormous success achieved thus far in stopping its spread. This study aimed to assess the demographics of COVID-19 patients from February to May 2021. Methods: Data were collected using secondary data from the medical records of Klungkung Regional General Hospital, Klungkung, at the time range according to the study period. Statistical Package for the Social Sciences (SPSS) version 25.0 for Windows and Microsoft Excel 2016 were used for the statistical analysis. All quantitative data, such as age, length of stay, and neutrophil-to-lymphocyte ratio (NLR), were estimated using central location measures (mean range). Proportions were used to describe qualitative or category variables. Results: The demographic description of COVID-19 patients at Klungkung Regional General Hospital, Klungkung, found an average age of 51.94 years old. More patients were found to be male (55.4%) and did not have comorbidities (55.3%). Fourteen patients (14.4%) were gravid, and 37 patients (17.8%) were treated in the Intensive Care Unit (ICU). A total of 61 patients (29.3%) had desaturase with an NLR (mean) of 6.97 (51% increase). The average length of stay was 10.16 days, with the result of 24 patients dying (11.5%). Conclusion: Patients with COVID-19 were found to have milder symptoms with less use of the ICU, not all of them experienced decreased saturation, and the case fatality rate was 11.5%.